Analysis of Economic Growth Before and After Changes in Tambaruni Market, Fakfak Regency - Agustina Waromi; Maraden R Tuturop; Everesta Klanit (Budapest International Research and Critics University, 2022)
Tambaruni market is a traditional market that has been used by the people of Fakfak district after the damage and fire of the Tambaruni market resulted in the weakening of the economic system in Fakfak district which was quite long from 2020 to 2022, this had an impact on the people's economy. The results of the study show thatThe test results obtained a t-count value of 0.879. In this study, hypothesis testing was carried out with a one-sided test because the alternative hypothesis (Ha) was a directed hypothesis. The value of the t-table on the degrees of freedom (dk) = 46 on the one-sided test, was obtained at 1.680. Based on the t-count value of 0.879 < t-table of 1.680, then Ho is accepted and Ha is rejected so that it is concluded that trading experience has no effect on the income of convection traders. Conclusion Trading capital has a positive and significant effect on the income of convection traders. Because capital is a very important factor for convection traders, the more capital used, the more diverse the merchandise and the more income will be obtained.